Translation and Its Features: Insight into Buddhist Aspects - Tamang, Kumar (Journal of Buddhist Studies (T.U.), 2025)
Translation is a complex cultural and epistemological act that goes beyond simple language use to support human communication and the transfer of knowledge across cultural boundaries. This research article critically analyzes the procedures, theoretical frameworks, historical development, and key features of translation, with an emphasis on Buddhist literature and translation tradition. It contends that translation requires doctrinal accuracy, cultural sensitivity, and linguistic in religious and philosophical contexts, especially Buddhism. Challenging the notion of impartial equivalency, the study explores how socio-cultural, interpretative, and ideological frameworks reshape meaning in translation. The central thesis posits that translation mediates between languages and worldviews in a communicative and reconstructive manner. Employing a qualitative descriptive methodology, it examines historical record, theoretical texts, and primary materials from Buddhist translation traditions in China, Tibet, and Nepal. This work assesses methodological approaches in Buddhist textual transmission by combining Skopos theory, Equivalence theory, and Cultural Translation theory. The findings highlight important aspects of translation, including it theoretical foundations, historical evolution, and subtle procedural aspects. The study concludes by highlighting translation as a culturally mediated activity that is essential to the spread of Buddhist teachings throughout the world.